PENGARUH PENGENDALIAN INTERN PENJUALAN KREDIT TERHADAP PIUTANG TAK TERTAGIH PADA PT. MULTI TOP INDONESIA CABANG TEBING TINGGI WILAYAH MEDAN - REBECCA EVADINE; DINA ROSMANELIANA; DIANTY PUTRI PURBA; DUMARIANI SILALAHI; HARLEN SILALAHI (JURNAL ILMIAH KOHESI, 2023)
Receivables are claims of a company on another party. Almost all entities have receivables from other parties, both related to sales or revenue transactions and represent receivables from other transactions. The purpose of this study was to determine the effect of credit sales internal control on bad debts at PT. Multi Top Indonesia, Tebing Tinggi Branch, Medan Region, 2017-2021. This type of research is descriptive quantitative with multiple linear regression analysis method. The results of this study indicate that there is a positive and significant influence between the internal control of credit sales on bad debts at PT. Multi Top Indonesia Tebing Tinggi Branch for the 2017-2021 period, with the results of the coefficient of determination test (R Square) obtained a value of 0.541 or the effect of internal control on credit sales on uncollectible accounts at PT. Multi Top Indonesia Branch Tebing Tinggi for the 2017-2021 period amounted to 54.1%.